Perovskite / crystalline silicon laminated solar cell and preparation method thereof
By introducing crosslinkable P-type small molecule materials during the perovskite layer film formation process to form an in-situ encapsulation layer, the problem of parasitic absorption of the HTL layer is solved, more efficient photocurrent conversion and stability are achieved, and calcium is improved Efficiency of titanite/crystalline silicon stacked solar cells.
Patent Information
- Application Number
- CN202411639286.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-11
AI Technical Summary
In existing perovskite/crystalline silicon stacked solar cells, parasitic absorption of the HTL layer leads to a decrease in photocurrent, limiting the improvement of battery efficiency.
By introducing crosslinkable P-type small molecule materials during the perovskite layer film formation process, an in-situ inner encapsulation layer is formed, replacing the traditional HTL layer, and an internal encapsulation structure is directly constructed on the surface of the perovskite layer.
It effectively reduces the parasitic absorption of the HTL layer, improves optical transmittance, enhances carrier transmission, and improves the stability of the device, significantly improving the efficiency of solar cells.
Smart Images

Figure CN119421623A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of tandem solar cells, and in particular to a perovskite / crystalline silicon tandem solar cell and a preparation method thereof. Background Art
[0002] With the rapid development of photovoltaic technology, the efficiency of single-junction perovskite solar cells has approached the Shockley-Queisser limit, limiting the space for further efficiency improvement. Perovskite / crystalline silicon tandem solar cells have become a hot topic of current research due to their ability to fully utilize the full spectrum of the sun. In this tandem structure, light first enters from one end of the perovskite subcell, and short-wavelength light is preferentially absorbed by the top perovskite cell, while long-wavelength light is directly transmitted to the bottom silicon cell and captured, thereby achieving efficient use of the spectrum.
[0003] In the design of NIP-type perovskite-crystalline silicon tandem solar cells, doped 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD) is usually used to prepare the hole transport layer (HTL) of high-efficiency devices due to its excellent hole transport properties. However, since the light of the tandem cell is incident from the transparent conductive electrode (TCO) on the top of the perovskite subcell and the HTL end, the optical properties of the HTL layer directly affect the light capture ability of the underlying perovskite and silicon layers. The existing spiro-OMeTAD layer is usually about 200 nm thick, and its parasitic absorption causes significant optical losses, resulting in a decrease in photocurrent, thereby limiting the efficiency of the cell. Therefore, how to effectively reduce the parasitic absorption of the HTL layer has become a key issue restricting the further development of NIP-type perovskite-crystalline silicon tandem solar cells.
[0004] In order to reduce the parasitic absorption of the HTL layer, the existing technology attempts to reduce the thickness of spiro-OMeTAD to about 80 nm. However, when the thickness is reduced to this level, the HTL layer shows uneven coverage on the perovskite surface, introducing serious composite defects at the perovskite / spiro-OMeTAD interface, which seriously hinders the transport of carriers. In addition, research on improving cell efficiency by replacing or doping other HTL materials has not shown a significant current gain effect. Therefore, how to further reduce the parasitic absorption of the top HTL layer and improve its stability has become a core issue in improving the efficiency of NIP-type perovskite / silicon stacked solar cells. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a perovskite / crystalline silicon laminated solar cell and a preparation method thereof, which introduces a cross-linkable P-type small molecule material as an additive to the stripping solvent during the film formation process of the perovskite layer to spontaneously form an in-situ inner encapsulation layer on the surface of the perovskite layer. The preparation method replaces the traditional process of step-by-step film formation of the perovskite absorption layer and the HTL layer, directly constructs an inner encapsulation structure on the surface of the perovskite layer, and solves the problems of parasitic absorption and poor stability caused by the thickness of the traditional HTL layer (such as spiro-OMeTAD, etc.).
[0006] The specific technical scheme of the present invention is: In a first aspect, the present invention provides a method for preparing a perovskite-crystalline silicon tandem solar cell, comprising the following steps: S1, depositing an electron transport layer on the surface of the silicon substrate battery; S2, spin coating a perovskite precursor solution on the surface of the electron transport layer in step S1, performing a stripping treatment using a solution containing a cross-linkable P-type small molecule material, and forming a perovskite absorption layer with an in-situ inner encapsulation layer after annealing; S3. On the perovskite absorption layer with the in-situ inner encapsulation layer described in step S2, a buffer layer, a transparent conductive electrode, a metal electrode and an anti-reflection layer are sequentially deposited to obtain a perovskite / crystalline silicon stacked solar cell.
[0007] The present invention provides a method for preparing a perovskite / crystalline silicon laminated solar cell by using a cross-linkable P-type small molecule material to perform an in-situ internal encapsulation strategy on perovskite without the need for additional HTL. The method uses a cross-linkable P-type small molecule material as an additive to a stripping solvent to participate in the formation process of perovskite. After annealing, the P-type small molecule material undergoes thermal cross-linking to form a polymer three-dimensional network, thereby realizing a perovskite structure in which the P-type small molecule material is in-situ encapsulated. The inner encapsulation perovskite structure formed by the above method has the following significant advantages: first, compared with the traditional perovskite / HTL step-by-step preparation, the present invention directly forms the inner encapsulation structure during the film formation process, without the need for an additional HTL step, thereby simplifying the process flow and significantly improving the preparation efficiency; second, the inner encapsulation layer has excellent optical transmittance, effectively solving the parasitic absorption problem caused by traditional top HTL materials (such as spiro-OMeTAD, etc.), and reducing optical losses; at the same time, the inner encapsulation layer effectively prevents the interface recombination problem caused by direct contact between the perovskite and the electrode; third, the inner encapsulation perovskite layer has good energy level matching, forming a good hole-selective contact, which is more conducive to efficient carrier transmission; finally, compared with the traditional HTL / perovskite structure, the inner encapsulation perovskite exhibits better stability.
[0008] In one possible embodiment, the P-type small molecule material includes at least one of the P-type small molecule materials having cross-linking properties: 4,4',4"-tri(N-carbazolyl)triphenylamine (TCTA-BVP), N,N'-di-p-tolyl-N,-N'-bis(4-vinylphenyl)-[1,1'-biphenyl]4,4'-diamine (Vp-TPD) and N4,N4 di(naphthalene-1-yl)-N4,N4'-bis(4-vinylphenyl)biphenyl-4,4'-diamine (VNPB).
[0009] In a possible implementation, the solvent of the solution containing the cross-linkable P-type small molecule material includes chlorobenzene.
[0010] In a possible implementation, the concentration of the solution containing the cross-linkable P-type small molecule material is 0.1-20 mmol / L.
[0011] In a possible implementation, the concentration of perovskite in the perovskite precursor solution is 0.5-2 mol / L.
[0012] In a possible implementation, the thickness of the in-situ inner encapsulation layer is 2-25 nm.
[0013] In a possible implementation, the step S2 specifically includes: spin coating a perovskite precursor solution on the surface of the electron transport layer, and dropwise adding the solution containing the cross-linkable P-type small molecule material, performing a stripping treatment, and after annealing, forming the perovskite absorption layer with an in-situ inner encapsulation layer.
[0014] Furthermore, the spin coating has a rotation speed of 1500-5000 rpm and a time of 30-60 s.
[0015] Furthermore, the annealing temperature is 90-160° C. and the annealing time is 10-60 min.
[0016] In a possible implementation, the step S1 specifically includes: depositing an electron transport layer thin film on the silicon substrate cell; and modifying the surface of the electron transport layer thin film using an interface modification material to obtain the electron transport layer.
[0017] In a possible implementation, the material of the electron transport layer includes at least one of SnO2, TiO2, and Nb2O5.
[0018] In a possible implementation, the electron transport layer is prepared by a physical deposition method or a chemical deposition method.
[0019] Furthermore, the thickness of the electron transport layer is 2-50 nm.
[0020] In a possible implementation, the interface modification material includes at least one of organic polymers, organic small molecules, self-assembled monolayer materials, inorganic materials, and ionic liquids.
[0021] In a possible implementation manner, the interface modification material is modified by a physical method or a chemical method.
[0022] Furthermore, the interface modification material is modified at a temperature ranging from room temperature to 200° C. and a time ranging from 0 to 60 min.
[0023] In a possible implementation, the step S3 specifically includes: depositing any one of molybdenum oxide, tungsten oxide and nickel oxide on the surface of the perovskite absorption layer with an in-situ inner encapsulation layer by a vacuum coating method or a solution method to form a buffer layer; then depositing a transparent conductive electrode on the buffer layer by a vacuum coating method; then depositing a metal electrode with a grid pattern on the transparent conductive electrode by any one of thermal evaporation, electroplating and screen printing processes; and finally depositing an anti-reflection layer on the surface of the transparent conductive electrode by an electron beam evaporation process.
[0024] The second aspect states that the present invention provides a perovskite / crystalline silicon stacked solar cell prepared by the above method, including a silicon base cell and a NIP-type perovskite top cell, wherein the NIP-type perovskite top cell includes an electron transport layer, an inner encapsulated perovskite layer, a buffer layer, a transparent conductive electrode, a metal electrode with a grid pattern and an anti-reflection layer, and the inner encapsulated perovskite layer is a perovskite light absorption layer treated with a cross-linkable P-type small molecule material.
[0025] Based on the common knowledge in this field, the above-mentioned implementation modes can be combined arbitrarily.
[0026] The reagents and raw materials used in the present invention are commercially available.
[0027] The positive and progressive effects of the present invention are: The present invention relates to a highly transparent hole-selective contact strategy without the need for additional HTL, and a method for preparing NIP-type perovskite / crystalline silicon stacked solar cells. The method involves adding cross-linkable P-type small molecules to an anti-solvent to participate in the perovskite film formation process, and after annealing, obtains a perovskite structure in which the cross-linkable P-type small molecule material is in-situ encapsulated, thereby achieving excellent hole-selective contact without the need for additional HTL. The present invention not only simplifies the device preparation process, but also effectively overcomes the serious parasitic absorption problem caused by the traditional top HTL (such as spiro-OMeTAD, etc.) in the NIP-type perovskite / crystalline silicon stacked device, while significantly improving the stability of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 These are transmission spectra of glass, the in-situ inner encapsulation layer prepared in Example 1, and the hole transport layer prepared in Comparative Example 1.
[0029] Figure 2 The fluorescence spectra of the bare perovskite and the perovskite absorption layer with an inner encapsulation layer prepared in Example 1 are shown.
[0030] Figure 3 This is a stability test comparison chart of the bare perovskite, the spiro-OMeTAD / perovskite prepared in Comparative Example 1, and the perovskite absorber layer with an inner encapsulation layer prepared in Example 1.
[0031] Figure 4 XRD patterns of the bare perovskite, the spiro-OMeTAD / perovskite prepared in Comparative Example 1, and the perovskite absorber layer with an inner encapsulation layer prepared in Example 1 before and after annealing at 85° C. for 1000 h. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present invention, and are not used to limit the parameter range described in the present invention. Reasonable changes derived therefrom are still within the scope of protection of the claims of the present invention.
[0033] It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0034] Unless otherwise defined, all terms, symbols and other scientific terms used herein are intended to have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. In some cases, terms with conventionally understood meanings are defined herein for the purpose of clarification or ease of reference, and such definitions herein should not be construed as indicating significant differences from conventional understandings in the art. The technical methods described or cited herein are generally well understood by those skilled in the art and are adopted by conventional methods. Unless otherwise stated, the use of commercially available kits, reagents and instruments is carried out in accordance with the protocols and parameters given by the manufacturer. Specific embodiments
[0036] Example 1
[0037] This embodiment provides a perovskite / crystalline silicon tandem solar cell, which is prepared by the following steps: S1. A 20 nm thick SnO2 layer was deposited on the Si bottom cell by ALD process, and then annealed in an air environment at 150 °C for 40 min. The surface of the SnO2 layer was treated with a UV cleaner, and then the surface of the ALD-SnO2 was modified with a 5 mmol / L potassium chloride aqueous solution to obtain an electron transport layer. S2, in step S1, the surface of the electron transport layer is spin-coated with 1 mol / L perovskite precursor solution, and a chlorobenzene solution of a cross-linkable P-type small molecule material with a concentration of 1 mmol / L is dripped onto the surface of the perovskite sample at a rotation speed of 2000 rpm to promote its rapid nucleation, and then the sample is transferred to a heating table and annealed at 150 ° C for 15 min to obtain a black-brown perovskite absorption layer with an in-situ inner encapsulation layer, and the thickness of the in-situ inner encapsulation layer is about 5 nm; S3. In step S2, a buffer layer is formed by depositing tungsten oxide on the surface of the perovskite absorption layer with an in-situ inner encapsulation layer by a thermal evaporation process; a transparent conductive electrode is then deposited on the buffer layer by a magnetron sputtering process; a metal electrode with a grid pattern is then deposited on the transparent conductive electrode by screen printing; and finally an anti-reflection layer is deposited on the surface of the transparent conductive electrode by an electron beam evaporation process, thereby obtaining a perovskite / crystalline silicon stacked solar cell.
[0038] Example 2 This embodiment provides a perovskite / crystalline silicon tandem solar cell, which is prepared by the following steps: S1. A 30 nm thick Nb2O5 layer was deposited on the Si bottom cell by ALD process, and then annealed in an air environment at 150 °C for 60 min. The surface of the Nb2O5 layer was treated with a UV cleaner, and a 5 mmol / LC 60 -SAM aqueous solution is used for surface modification to obtain an electron transport layer; S2, in step S1, the surface of the electron transport layer is spin-coated with 1.3 mol / L perovskite precursor solution, and a chlorobenzene solution of a cross-linkable P-type small molecule material with a concentration of 8 mmol / L is dripped onto the surface of the perovskite sample at a rotation speed of 3000 rpm to promote its rapid nucleation, and then the sample is transferred to a heating table and annealed at 150 ° C for 20 min to obtain a black-brown perovskite absorption layer with an in-situ inner encapsulation layer, and the thickness of the in-situ inner encapsulation layer is about 8 nm; S3. In step S2, a buffer layer is formed by depositing molybdenum oxide on the surface of the perovskite absorption layer with an in-situ inner encapsulation layer by a thermal evaporation process; a transparent conductive electrode is then deposited on the buffer layer by a magnetron sputtering process; a metal electrode with a grid pattern is then deposited on the transparent conductive electrode by a thermal evaporation process; and finally an anti-reflection layer is deposited on the surface of the transparent conductive electrode by an electron beam evaporation process, thereby obtaining a perovskite / crystalline silicon stacked solar cell.
[0039] Example 3
[0040] This embodiment provides a perovskite / crystalline silicon tandem solar cell, which is prepared by the following steps: S1. A 40 nm thick SnO2 layer was deposited on the Si bottom cell by CBD process, and then annealed in an air environment at 180 °C for 60 min. The surface of the SnO2 layer was treated with a UV cleaner, and then the CBD-SnO2 surface was modified with an aqueous solution of ammonium fluoride at a concentration of 2 mmol / L to obtain an electron transport layer. S2, in step S1, the surface of the electron transport layer is spin-coated with 1.5 mol / L perovskite precursor solution, and a chlorobenzene solution of a cross-linkable P-type small molecule material with a concentration of 10 mmol / L is dripped onto the surface of the perovskite sample at a rotation speed of 4000 rpm to promote its rapid nucleation, and then the sample is transferred to a heating table and annealed at 100 °C for 30 min to obtain a black-brown perovskite absorption layer with an in-situ inner encapsulation layer, and the thickness of the in-situ inner encapsulation layer is about 10 nm; S3. In step S2, nickel oxide is deposited on the surface of the perovskite absorption layer with an in-situ inner encapsulation layer by a thermal evaporation process to form a buffer layer; a transparent conductive electrode is then deposited on the buffer layer by a magnetron sputtering process; a metal electrode with a grid pattern is then deposited on the transparent conductive electrode by a thermal evaporation process; and finally an anti-reflection layer is deposited on the surface of the transparent conductive electrode by an electron beam evaporation process, thereby obtaining a perovskite / crystalline silicon stacked solar cell.
[0041] Comparative Example 1 This comparative example provides a perovskite-crystalline silicon tandem solar cell, which is different from Example 1 in that: S2, in step S1, the surface of the electron transport layer is spin-coated with 1.3 mol / L perovskite precursor solution at a rotation speed of 3000 rpm, and then annealed at 150 °C for 15 min to form a perovskite layer; then the surface of the perovskite absorption layer is spin-coated with spiro-OMeTAD material solution to form a hole transport layer, thereby obtaining spiro-OMeTAD / perovskite; S3. In step S2, molybdenum oxide is deposited on the surface of the hole transport layer by a thermal evaporation process to form a buffer layer; then a transparent conductive electrode is deposited on the buffer layer by a magnetron sputtering process; a metal electrode with a grid pattern is subsequently deposited on the transparent conductive electrode by a thermal evaporation process; and finally an anti-reflection layer is deposited on the surface of the transparent conductive electrode by an electron beam evaporation process, thereby obtaining a perovskite / crystalline silicon stacked solar cell with an additional hole transport layer.
[0042] Effect Example
[0043] Figure 1 These are the transmittance spectra of glass (glass), the in-situ inner encapsulation layer (target) prepared in Example 1, and the spiro-OMeTAD layer (spiro-OMeTAD) prepared in Comparative Example 1. It can be seen from the figure that, compared with the spiro-OMTAD layer, the in-situ inner encapsulation layer has more excellent optical transmittance in the full spectrum band, especially in the short wavelength band.
[0044] Figure 2 The fluorescence spectra of the bare perovskite (control) and the perovskite absorption layer with an inner encapsulation layer (target) prepared in Example 1. Lower fluorescence intensity means that more carriers are quenched. It can be seen from the figure that compared with the bare perovskite, the inner encapsulated perovskite can extract carriers more efficiently, resulting in a rapid decay of the fluorescence intensity.
[0045] Figure 3 This is a stability test comparison chart of bare perovskite (control), spiro-OMeTAD / perovskite (spiro-OMeTAD) prepared in Comparative Example 1, and the perovskite absorption layer with an inner encapsulation layer prepared in Example 1 (target). It can be seen from the figure that the inner encapsulated perovskite does not change after being flushed with water, which means that its good hydrophobicity can effectively prevent water vapor from corroding and damaging the perovskite.
[0046] Figure 4 The XRD patterns of bare perovskite (control), spiro-OMeTAD / perovskite (spiro-OMeTAD) prepared in Comparative Example 1, and the perovskite absorber layer with an inner encapsulation layer (target) prepared in Example 1 before and after annealing at 85°C for 1000 h. It can be seen from the figure that before and after annealing, the XRD characteristic peaks of bare perovskite and spiro-OMeTAD / perovskite change greatly, while the XRD characteristic peaks of the inner encapsulated perovskite change little, indicating that the inner encapsulated perovskite has the best thermal stability.
[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a perovskite / crystalline silicon tandem solar cell, characterized in that: The following steps are involved: S1, depositing an electron transport layer on the surface of the silicon substrate battery; S2, spin coating a perovskite precursor solution on the surface of the electron transport layer in step S1, performing a stripping treatment using a solution containing a cross-linkable P-type small molecule material, and forming a perovskite absorption layer with an in-situ inner encapsulation layer after annealing; S3. On the perovskite absorption layer with the in-situ inner encapsulation layer described in step S2, a buffer layer, a transparent conductive electrode, a metal electrode and an anti-reflection layer are sequentially deposited to obtain a perovskite / crystalline silicon stacked solar cell.
2. The method for preparing a perovskite / crystalline silicon tandem solar cell according to claim 1, characterized in that: The cross-linkable P-type small molecule material includes at least one of the P-type small molecule materials with cross-linking properties, including 4,4',4"-tri(N-carbazolyl)triphenylamine, N,N'-di-p-tolyl-N,-N'-bis(4-vinylphenyl)-[1,1'-biphenyl]4,4'-diamine and N4,N4 di(naphthalene-1-yl)-N4,N4'-bis(4-vinylphenyl)biphenyl-4,4'-diamine.
3. The method for preparing the perovskite / crystalline silicon tandem solar cell according to claim 1, characterized in that: The solvent of the solution containing the cross-linkable P-type small molecule material includes chlorobenzene; And / or, the concentration of the solution containing the cross-linkable P-type small molecule material is 0.1-20 mmol / L.
4. The method for preparing a perovskite / crystalline silicon tandem solar cell according to claim 1, characterized in that: The concentration of perovskite in the perovskite precursor solution is 0.5-2 mol / L; And / or, the thickness of the in-situ inner encapsulation layer is 2-25 nm.
5. The method for preparing a perovskite / crystalline silicon tandem solar cell according to claim 1, characterized in that: The step S2 specifically includes: spin coating the perovskite precursor solution on the surface of the electron transport layer, and dropwise adding the solution containing the cross-linkable P-type small molecule material, performing a stripping treatment, and after annealing, forming the perovskite absorption layer with the in-situ inner encapsulation layer.
6. The method for preparing the perovskite / crystalline silicon tandem solar cell according to claim 5, characterized in that: The spin coating has a rotation speed of 1500-5000 rpm and a time of 30-60 s; And / or, the annealing temperature is 90-160° C. and the annealing time is 10-60 min.
7. The method for preparing a perovskite / crystalline silicon tandem solar cell according to claim 1, characterized in that: The step S1 specifically includes: depositing an electron transport layer thin film on the silicon substrate cell; and modifying the surface of the electron transport layer thin film by using an interface modification material to obtain the electron transport layer.
8. The method for preparing the perovskite / crystalline silicon tandem solar cell according to claim 7, characterized in that: The material of the electron transport layer includes at least one of SnO2, TiO2, and Nb2O5; And / or, the electron transport layer is prepared by a physical deposition method or a chemical deposition method; And / or, the thickness of the electron transport layer is 2-50 nm; and / or, the concentration of the interface modification material is 0-30 mmol / L; And / or, the interface modification material includes at least one of organic polymers, organic small molecules, self-assembled monolayer materials, inorganic materials, and ionic liquids; and / or, the interface modification material is modified by a physical or chemical method; And / or, the interface modification material is modified at a temperature ranging from room temperature to 200° C. and a time ranging from 0 to 60 min.
9. The method for preparing a perovskite / crystalline silicon tandem solar cell according to claim 1, characterized in that: The step S3 specifically includes: depositing any one of molybdenum oxide, tungsten oxide and nickel oxide on the surface of the perovskite absorption layer with an in-situ inner encapsulation layer by a vacuum coating method or a solution method to form a buffer layer; then depositing a transparent conductive electrode on the buffer layer by a vacuum coating method; then depositing a metal electrode with a grid pattern on the transparent conductive electrode by any one of thermal evaporation, electroplating and screen printing processes; and finally depositing an anti-reflection layer on the surface of the transparent conductive electrode by an electron beam evaporation process.
10. The perovskite / crystalline silicon tandem solar cell prepared according to the method for preparing a perovskite / crystalline silicon tandem solar cell according to any one of claims 1 to 9, characterized in that: It includes a silicon base cell and a NIP type perovskite top cell, wherein the NIP type perovskite top cell includes an electron transport layer, an inner encapsulated perovskite layer, a buffer layer, a transparent conductive electrode, a metal electrode with a grid pattern and an anti-reflection layer, and the inner encapsulated perovskite layer is a perovskite light absorption layer treated with a cross-linkable P-type small molecule material.
Citation Information
Patent Citations
Perovskite solar cell and rapid preparation method thereof
CN115768222A
Flexible perovskite solar cell based on small organic molecules capable of in-situ crosslinking
CN115942852A
Perovskite thin film, preparation method thereof and hole transport layer-free p-i-n type perovskite device
CN116156983A
N-I-P perovskite / silicon laminated solar cell and preparation method thereof
CN116367563A
Polymer cross-linking packaging method of perovskite solar cell
CN118678839A